Regulation and Functions of the ER-Associated Nrf1 Transcription Factor - Ruvkun, Gary; Lehrbach, Nicolas (Cold Spring Harbor perspectives in biology, 2023)
Nrf1 is a member of the nuclear erythroid 2-like family of transcription factors that regulate stress-responsive gene expression in animals. Newly synthesized Nrf1 is targeted to the endoplasmic reticulum (ER) where it is -glycosylated. -glycosylated Nrf1 is trafficked to the cytosol by the ER-associated degradation (ERAD) machinery and is subject to rapid proteasomal degradation. When proteasome function is impaired, Nrf1 escapes degradation and undergoes proteolytic cleavage and deglycosylation. Deglycosylation results in deamidation of -glycosylated asparagine residues to edit the protein sequence encoded by the genome. This truncated and "sequence-edited" form of Nrf1 enters the nucleus where it induces up-regulation of proteasome subunit genes. Thus, Nrf1 drives compensatory proteasome biogenesis in cells exposed to proteasome inhibitor drugs and other proteotoxic insults. In addition to its role in proteasome homeostasis, Nrf1 is implicated in responses to oxidative stress, and maintaining lipid and cholesterol homeostasis. Here, we describe the conserved and complex mechanism by which Nrf1 is regulated and highlight emerging evidence linking this unusual transcription factor to development, aging, and disease.